1971
DOI: 10.1111/j.2044-8260.1971.tb00729.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Psychoticism’ in Drug‐Users

Abstract: Scores on the PEN Inventory were obtained from four groups of drug‐users. They were compared with scores from a group of apprentices who had completed the Inventory non‐anonymously rather than the normative data, as the latter were obtained anonymously, and it was found that this factor significantly elevated P (‘psychoticism’) scores. All four groups were significantly higher on P than the comparison groups. This was not simply the result of endorsement of items directly related to drug‐taking, nor to the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The other 'abnormality' scale on the EPQ (P), contributed nine out ofthe 32 items. Five of these items could be seen as a willingness to reject conventional social values (items 2,9,18,57,74). The other P items are either directly related, or could be seen as indirectly related to the use of drugs, (most obviously, item 22 which concerns drug taking, but also items 30 and 65.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other 'abnormality' scale on the EPQ (P), contributed nine out ofthe 32 items. Five of these items could be seen as a willingness to reject conventional social values (items 2,9,18,57,74). The other P items are either directly related, or could be seen as indirectly related to the use of drugs, (most obviously, item 22 which concerns drug taking, but also items 30 and 65.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that drug dependent groups are characterised by high levels of neuroticism and psychoticism and by low levels of extraversion, [1,2]. Other studies of drug users have also suggested that personality factors of this sort may be implicated in drug use.…”
mentioning
confidence: 99%
“…Is it true that addictive behaviour is largely determined by P, and to a smaller extent by N (neuroticism)? Early studies by Gossop (1978) and Teasdale et al (1971) showed that drug-dependent groups had typically high levels of psychoticism, together with elevated scores on neuroticism; they also had somewhat lower levels of extraversion than controls.…”
Section: Personality and Addictionmentioning
confidence: 99%
“…A second critical remark that is often made concerns the fact that high P scores can be found in criminals (Eysenck and Eysenck, 1976) and other non-psychotic persons with socially deviant behaviour, including drug addicts (Teasdale, Segraves and Zacune, 1971;Wells and Stacey, 1976) and alcoholics (Shaw, MacSweeney, Johnson and Merry, 1975). T o most critics this had proved that the EPQ-P scale could not be a valid measure of Psychoticism.…”
Section: Introductionmentioning
confidence: 99%